Accumulation of α-Synuclein in Cerebellar Purkinje Cells of Diabetic Rats and Its Potential Relationship with Inflammation and Oxidative Stress Markers - Volkan Solmaz; Hatice Köse Özlece; Hüseyin Avni Eroglu; Hüseyin Aktuğ; Oytun Erbaş; Dilek Taşkıran (Neurology Research International)
Objective. The present study was conducted to evaluate the relationship between plasma oxidative stress markers such as malondialdehyde (MDA) and glutathione (GSH), inflammatory marker pentraxin-3 (PTX3), and cerebellar accumulation of α-synuclein in streptozotocin- (STZ-) induced diabetes model in rats. Methods. Twelve rats were included in the study. Diabetes (n=6) was induced with a single intraperitoneal injection of streptozotocin (STZ, 60 mg/kg). Diabetes was verified after 48 h by measuring blood glucose levels. Six rats served as controls. Following 8 weeks, rats were sacrificed for biochemical and immunohistochemical evaluation. Results. Plasma MDA levels were significantly higher in diabetic rats when compared with the control rats (p<0.01), while plasma GSH levels were lower in the diabetic group than in the control group (p<0.01). Also, plasma pentraxin-3 levels were statistically higher in diabetic rats than in the control rats (p<0.01). The analysis of cerebellar α-synuclein immunohistochemistry showed a significant increase in α-synuclein immunoexpression in the diabetic group compared to the control group (p<0.01). Conclusion. Due to increased inflammation and oxidative stress in the chronic period of hyperglycemia linked to diabetes, there may be α-synuclein accumulation in the cerebellum and the plasma PTX3 levels may be assessed as an important biomarker of this situation.